2016
DOI: 10.1159/000444536
|View full text |Cite
|
Sign up to set email alerts
|

Association between Urinary Sodium Excretion and Bone Health in Male and Female Adults

Abstract: Background: High salt intake is a well-known risk factor for osteoporosis, but the association between bone mass and urinary sodium excretion has not been studied as yet. This study investigates the hypothesis that urinary sodium excretion is negatively associated with bone mass and the risk of osteoporosis. Methods: This cross-sectional study was performed using data from the Korea National Health and Nutrition Examination Survey, 2008-2011. Participants (n = 16,279) were divided into age groups; men were cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 21 publications
0
11
0
1
Order By: Relevance
“…Excessive sodium intake, as translated by salt consumption, is a known risk factor for osteoporosis. However, a study demonstrated urinary sodium excretion and bone health are negatively correlated [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Excessive sodium intake, as translated by salt consumption, is a known risk factor for osteoporosis. However, a study demonstrated urinary sodium excretion and bone health are negatively correlated [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…These studies are summarized in Table . The outcomes examined were diverse: one study assessed mortality outcomes (category I), two studies assessed morbidity outcomes (category II), two studies assessed outcomes related to symptoms/quality of life/functional status (category III), six studies assessed BP outcomes (category IV), seven studies assessed other clinically relevant surrogate outcomes (category V), and 10 studies assessed physiologic outcomes (category VI) …”
Section: Resultsmentioning
confidence: 99%
“…No primary research studies in the physiologic category (category VI) met the minimum methodological criteria. A range of outcomes were captured by the studies considered to be of lower quality, including all‐cause mortality, headaches/migranes, BP, cognitive function, acne, obesity and ghrelin, multiple sclerosis, BMD, gastric cancer, flow‐mediated dilatation, pulse wave velocity, markers of the renin‐angiotensin‐aldosterone system, heart rate, insulin resistance and the metabolic syndrome, brain tissue white matter hyperintensity, uric acid, and urinary albumin . Most of these studies found adverse effects of dietary salt on health, except for three that were neutral and one that found an inverse relationship between salt intake and headaches/migranes …”
Section: Resultsmentioning
confidence: 99%
“…In the HF group, detailed information on the 25-hydroxyvitamin D (25(OH)D) assay was provided previously ( 9 ). Serum 25(OH)D levels were determined with a radioimmunoassay kit (DiaSorin, Stillwater, MN, USA).…”
Section: Methodsmentioning
confidence: 99%